(untitled) (Italian Journal of Public Health, 2010)
Aim: The aim of this study was to find out at what age children start smoking, as well as their tobacco habits and risk perceptions according to the different school-age groups. Methods: A cross-sectional survey was carried out in 2007; it involved around 1700 students of the Catania province, in Southern Italy. The students filled in a structured tobacco questionnaire. They did it anonymously in the classrooms. Main outcome measures were initiation of smoking, smoking habits, number of cigarettes smoked per day and risk perception. Results: From the first year of the primary school to the last year of the high school the proportion of daily smokers increased from 0.0% to 11.8% for girls and from 0.8% to 12.7% for boys. For both genders the initiation of smoking habits occurred mainly at age 10 to 13. Finally, girls had a better risk perception. Conclusions: Studying young people’s tobacco habits over time gives an understanding of when preventive measures have to be implemented. In order to influence smoking attitudes, these preventive interventions must be put in place before children start experimenting tobacco.